Dampak Implementasi GATT/WTO terhadap Ekspor Impor Indonesia - Kadarukmi, M.E. Retno (Business Administration Study Program - Universitas Katolik Parahyangan, 2013)
Although Indonesia has been a member of the World Trade Organization (WTO),but in fact the Indonesian trade, especially with regard to the export-import in thefree trade has not been established. This happens due to the competitiveness of theIndonesian national product is still weak. Nevertheless, as a consequence of Indonesiahas ratified the GATT / WTO, the government should try to improve the competitive-ness of national products through the Indonesian national law reform to formulatea Trade Policy that refers to the national interests of Indonesia, through the Law onAnti-Dumping and Safeguard.Keywords: Export, import, free trade, GATT/WTO.